Management Roles in Promoting Safety Awareness among Teaching Staff in TVET Institutions - Ahmad, Shanusi; Md Yunos, Jailani; Zulkifly, Syazwan Syah; Mohd Yaakob, Mohd Faiz; Mohamad Zain, Affendy Zabkha; Hasan, Nor Halim (Journal of Technical Education and Training, 2024)
The recent government focus on Technical Vocational Education and Training (TVET) underscores its pivotal role in developing a highly skilled workforce. TVET institutions primarily offer diploma and certificate courses in technical and vocational fields, which involve teaching and learning activities in workshops and laboratories. These settings pose inherent hazards which present risks to both students and staff. Therefore, ensuring safety awareness is essential to prevent industrial accidents. This quantitative cross-sectional study examines the impact of the management's roles in promoting safety awareness among teaching staff in selected Government TVET Institutions. The study focuses on three critical independent variables representing the management's duties: safety policy, safety and health committee functions, and safety training. Data were collected through self-administered questionnaires distributed to 119 teaching staff across four institutions in the central, northern, and east-coast regions of Peninsular Malaysia. The findings highlight the significant role of management in shaping safety awareness among teaching staff within Government TVET Institutions. Based on these results, it is recommended that institutions prioritize implementing robust safety policies, enhancing the effectiveness of safety and health committees, and investing in comprehensive safety training programs to further increase safety awareness levels among staff members.